Susceptibilidade a desertificação no alto curso da sub-bacia do Rio Canindé (Ceará, Brasil) - Soares, Larisse Freitas (2023)
Desertification has been occurring significantly in the semi-arid region of Ceará, causing socio-environmental impacts, such as the loss of the land's productive capacity. This phenomenon, above all, is intensified by the use and occupation of land, in the face of society's pressure on natural resources. The main objective is to evaluate the susceptibility to desertification in the upper reaches of the Canindé River sub-basin, Ceará/Brazil through geobiophysical indicators of desertification. The specific objectives are outlined below: delimit and characterize the geoenvironmental components and environmental systems of the sub-basin; measure the percentage of degraded and/or desertified areas present in the study areas; identify the forms of occupation and use of land, and their implications for the quality of life of the local population; characterize the landscape to define its potential and limitations through geobiophysical indicators of desertification. Regarding theoretical and methodological aspects, the research was developed based on systemic analysis, which, through integrated landscape studies, considers the interaction between the elements of ecological potential, biological exploration and anthropic action, and the application of Geobiophysical Indicators of Desertification (IGBD) aim to aggregate new areas susceptible to desertification of the study objects. The research is structured in the following stages: bibliographical survey, where documentary research was developed, data collection, cartographic survey and preparation of thematic cartography and, in the field, and synthesis stage, with the elaboration of thematic mapping. The following results were obtained: the delimitation of environmental systems, the identification of environmental systems prone to desertification, that is, the backlands, residual ridges and inselbergs, which are the most vulnerable. It was found that the desertification process directly interferes with socioeconomic conditions, especially during dry years, resulting in a reduction in agricultural and extractive production, even with an increase in harvesting areas. This leads to an increase in production costs for the inhabitants of the hinterland. Therefore, it is necessary to implement public policies for the use of natural resources in the semi-arid region, in order to mitigate the effects of environmental degradation.